Implementasi Sistem E-Procurement di Dinas Perindustrian dan Perdagangan Aceh: Tantangan dan Strategi Optimalisasi - Depita Kardiati (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The use of information and communication technology (ICT) in procurement services is one of the efforts to realize good governance. The electronic procurement system is present by simplifying the stages of the procurement process, the vendor search stage, price comparison from each vendor, approval, monitoring, billing, to payment, all of which are done digitally. Thus, it is hoped that procurement activities for goods/services will be carried out with good procurement principles, namely effective, efficient, transparent, open, competitive, fair, and accountable. This study aims to analyze the implementation of an electronic-based procurement system for goods/services at the Aceh Industry and Trade Service and the obstacles faced in its implementation. The research method used is descriptive qualitative with data collection through interviews, observations, and documentation. The results of the study indicate that although the electronic-based procurement system can increase the transparency and efficiency of the procurement process, its implementation still faces challenges such as limited technological infrastructure and lack of technical competence of human resources. The implications of these findings indicate the need to increase human resource capacity and strengthen ICT infrastructure to support more optimal implementation.